WarDriving & wireless penetration testing - Hurley, Chris (Syngress Pub., 2007)
Wireless networking has become standard in many business and government networks. Aimed primarily at those individuals that are tasked with performing penetration testing on wireless networks, this book focuses on the methods used by professionals to perform WarDriving and wireless penetration testing.